El movimiento obrero y las izquierdas en América Latina : experiencias de lucha, inserción y organización. - Camarero, Hernán; Mangiantini, Martín, 1979- (Serie Historia y ciencias sociales., 2018)
The labor movement and the left are part of the history of Latin America. There are almost no dimensions of society, economy, politics, culture or the intellectual field of most of the countries of the subcontinent that can be understood without the intervention of one of these two actors. The relational approach is essential here. Anarchists, socialists, communists, revolutionary syndicalists, Trotskyists, Maoists and Guevarists, among others, were political-ideological expressions whose investigation cannot be genuinely achieved without a global approach to the working classes. This book is intended to be a contribution in this direction. It constitutes an approximation to the most recent elaborations around these topics. It brings together texts prepared by qualified researchers from a dozen countries, offering, jointly and comparatively, elements that contribute to a global and renewed vision of the subject based on case studies in which common problems are addressed.